Evaluation of the efficacy of ethanol, peracetic acid, and quaternary ammonium compounds against murine norovirus using carrier and suspension tests. (January 2023) - Min, Ae; Hossain, Md Iqbal; Jung, Soontag; Yeo, Daseul; Wang, Zhaoqi; Song, Mengxiao; Zhao, Ziwei; Park, Sunho; Choi, Changsun
Abstract: Virucidal suspension testing is commonly used as an authorized test for disinfectants. However, this method could not precisely evaluate the effect of disinfectants on food-contact surfaces. To solve this problem, a carrier testing method needs to be established in the food-processing industries by following a standard guideline. Therefore, we employed two murine norovirus strains (MNV-1 and MNV-S99) to evaluate the antiviral efficacy of three disinfectants, i.e., ethanol, peracetic acid (PAA), and quaternary ammonium compounds (QACs) after three contact times (1, 5 and 10 min) as per the OECD guidelines regarding the carrier test. Following this, we compared the results of carrier testing results with those of suspension testing. The standard level of antiviral efficacy for disinfectants was determined by ≥ 3 log10 (99.9%) and ≥4 log10 (99.99%) reduction of viral titers in carrier and suspensions tests, respectively. In the carrier test, ethanol and PAA were effective against both MNVs and showed the standard level of performance at selected concentrations and contact times; the exception being the highest concentration of ethanol (90% for all contact times) and lowest concentration of PAA (80 ppm for 1 min). QACs were not effective against both MNVs at all selected concentrations and contact times. In the case of suspension test, ethanol and PAA exhibited the best antiviral efficacy and showed the standard level of performance at all contact times and concentrations; while, all concentrations of QACs were not enough to reduce the MNV-1 titers for achieving the standard level of performance during experimental conditions. This study showed that ethanol and PAA could inactivate MNVs under surface and suspension conditions. Therefore, these results could provide valuable information for establishing standard antiviral efficacy tests and approaches to control viral transmission via surfaces. Highlights: Ethanol and PAA could inactivate MNVs under surface and suspension conditions. QACs were not effective against MNV in carrier or suspension tests. Similar results were obtained for these agents in the carrier and suspension tests. Carrier test was better than suspension test to measure surface disinfectant levels.